2017
DOI: 10.1002/jsfa.8759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Posidonia oceanica banquettes on intake, digestibility, nitrogen balance and metabolic profiles in sheep

Abstract: Moderate quantities of barley straw (between 75 and 150 g day per ewe) can be replaced by PO in feed rations for mature ewes. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…For goats, supplementation with PO showed that this animal was able to consume daily up to 450g/day without any detrimental effect at the productive level [12]. While for Merino sheep the optimal intake the ideal proportion to supplement was between 75 and 150g (as a limit) of PO/day [13].…”
Section: Results Obtained With the Use Of Posidonia Oceanica Residues On Small Ruminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…For goats, supplementation with PO showed that this animal was able to consume daily up to 450g/day without any detrimental effect at the productive level [12]. While for Merino sheep the optimal intake the ideal proportion to supplement was between 75 and 150g (as a limit) of PO/day [13].…”
Section: Results Obtained With the Use Of Posidonia Oceanica Residues On Small Ruminantsmentioning
confidence: 99%
“…If it was a common fact for both species the need of a time of adaptation to the product (which was never more than one week) and that the animals showed preferences for the dry plant, never wet. We consider this management factor to be of vital importance when introducing this fodder source in the new rations, which should be introduced progressively [13]. The marine plant contains more ashes than cereal or hay straw; the lignin fraction is also higher than reported values for straw, hay or silage [11] although its ruminal degradability is greater [9].…”
Section: Results Obtained With the Use Of Posidonia Oceanica Residues On Small Ruminantsmentioning
confidence: 99%
“…In addition to its richness in antioxidant agents, P. oceanica contains antibacterial agents proved to be very active against Gram+, Gram-, dermatophytes and yeast that can be exploited to fight infections (Haznedaroglu and Zeybek 2007;Abdelmohsen et al 2016). Castillo et al (2017) confirmed that the incorporation of such natural products rich in antioxidant and antibacterial agents in livestock rations could reduce the use of antibiotics.…”
Section: Discussionmentioning
confidence: 73%
“…After complete replacement of barley straw by P. oceanica in Murciano-Granadina goats' ration, no significant difference was found in the main physico-chemical and sensory parameters of the resulting milk and cheese (Eldik et al 2017). Similarly, Castillo et al (2018) observed no negative effects on dry matter intake, final body weight and metabolic status of adult Merino ewes when 15% of the barley straw was replaced by P. oceanica. However, they did notice an improvement in nitrogen utilization.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation